The Influence of Iban Students’ Motivation on the Achievement in the Malay Language Subject as a Second Language - Maureen Sait; Saripah Banseng; Doratya Gerry; Puteri Zarina Megat Khalid; Nur Faaizah Md-Adam; Ciptro Handrianto (International Journal of Education, Information Technology, and Others, 2023)
Learning Malay as a second language is not a simple process for non-native students, particularly Iban students. The study was conducted to look at the influence of Iban students’ motivation on the achievement in the Malay Language subject as a second language. A survey was conducted among fifty Form 4 Iban students at a national secondary school in Betong, Sarawak. A total of 27 questions were included in the set of questionnaires utilised as the instrument for this stud. y, which comprised motivational influence variables from one's self, family, environment, and peers. The data in this study was analysed using the descriptive and the inferential statistical methods via the Statistical Package for Social Science (SPSS) version 25. The study found that the level of motivating influence of Iban students was high. However, the Pearson’s correlation analysis result showed that there is no significant association between the motivating influence of Iban students and their level of achievement in Malay Language’s subject as their second language. Thus, motivation is not a dominant factor that influences the Iban students’ achievement in the subject.